Impact of Haemodialysis: Analysis of Haemoglobin Levels and Blood Pressure Control in Patients with End-Stage Renal Disease - Bangun, Argi Virgona; Baroka, Nurani Saxena; Santoso, M. Budi (STIKep PPNI Jawa Barat, 2024)
Aims: To analyze the effect of hemodialysis on hemoglobin levels and blood pressure in patients with End Stage Renal Disease (ESRD). Method: The study used a one-group pretest-posttest design with 17 respondents. Data were collected using EDTA tubes, sphygmomanometers, and stethoscopes. A paired t-test and Wilcoxon signed-rank test were applied to analyze the significance of changes between pretest and posttest results Results: The mean hemoglobin level before hemodialysis was 7.92 g/dL and increased to 8.50 g/dL after hemodialysis (p = 0.001). The mean systolic blood pressure decreased from 136.6 mmHg before to 124.0 mmHg after hemodialysis (p = 0.003). However, there was no significant difference in diastolic blood pressure, with an average of 80.6 mmHg before and 78.6 mmHg after hemodialysis (p = 0.180). Conclusion: It can be concluded that hemodialysis significantly increases hemoglobin levels and reduces systolic blood pressure in ESRD patients, while diastolic blood pressure remains unchanged. Regular monitoring of hemoglobin and systolic blood pressure is crucial for managing patient health. Hemodialysis effectively raises hemoglobin levels and reduces systolic blood pressure in ESRD patients. Regular monitoring of both parameters is essential for effective patient management. While the findings highlight the benefits of hemodialysis, the limited sample size may restrict the generalizability of the results. Further studies with larger sample sizes are needed to confirm these findings and explore the long-term implications.